2011
DOI: 10.1016/j.applthermaleng.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of diameter effect on heat transfer of supercritical water flows in horizontal round tubes

Abstract: The diameter effect on the heat transfer of supercritical water (SCW) flows in horizontal round tubes has been studied using computational fluid dynamics (CFD) technique. The numerical simulations are carried out by the STAR-CD solver combined with the user developed subroutines that control the numerical calculation procedures.Through the tests it is found that the discretization scheme using CD, LUD or MARS will not affect the accuracy of the numerical simulations. Through the diameter effect studies, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For numerical method, indeed there have developed several kinds for supercritical fluid modeling in literature, including computational fluid dynamics models based on finite volume, or finite difference models [34,35], or lattice Boltzmann method [36] and others [37]. Following those studies, finite-volume method and a second-order upwind scheme are used to solve the model goveming equations.…”
Section: Methodsmentioning
confidence: 99%
“…For numerical method, indeed there have developed several kinds for supercritical fluid modeling in literature, including computational fluid dynamics models based on finite volume, or finite difference models [34,35], or lattice Boltzmann method [36] and others [37]. Following those studies, finite-volume method and a second-order upwind scheme are used to solve the model goveming equations.…”
Section: Methodsmentioning
confidence: 99%
“…Kao et al [22] concluded that buoyancy effect and Prandtl number play important roles in heat transfer deterioration of supercritical water inside vertical circular tubes. Shang and Chen [23] investigated the diameter effect on heat transfer. For supercritical fluid calculation, the turbulence model undoubtedly plays a key role in the simulations and the model selection is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of buoyancy is often minimal for a very small diameter tube due to the small Richardson number (i.e. below unity) [124]. A Richardson number of lower than 0.087 is observed for the investigated cases, and therefore, the gravitational force can be neglected.…”
Section: Methodsmentioning
confidence: 85%
“…The natural convection plays an important role in a supercritical flow with low mass flux, see [102,123,124] for further information. The Grashof number can be applied to quantify the influence of buoyancy to the flow field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation